Identifying the Dimensions of the Teacher-Student Relationship Construct - Azad, Somayeh; Akhavan Tafti, Mahnaz; Mohsenpour, Maryam (Iranian Journal of Educational Sociology, 2022)
Purpose: This study aims to develop a comprehensive scale for assessing the teacher-student relationship by integrating elements from various established theories in educational psychology.Methodology: The study employed a systematic review approach, following the framework by Oakley and Shabrams (2010), to synthesize dimensions from attachment theory, interpersonal theory, social support theory, and self-determination theory. Items for each dimension were adapted from existing validated questionnaires. The initial scale comprised 80 items and was subjected to face and content validity assessment by an expert panel. Content Validity Ratio (CVR) and Content Validity Index (CVI) were calculated to ensure the relevance and essentiality of the items.Findings: Six core dimensions were identified: emotional support, conflict, autonomy and independence, self-worth and competence, instrumental support, and informational support. The final student version comprised 32 items, while the teacher version included 30 items. The validation process confirmed that the items accurately reflect the theoretical constructs and are relevant to the educational context. The findings align with existing literature, emphasizing the importance of emotional and instrumental support, effective conflict management, and the role of autonomy in enhancing student engagement and academic performance.Conclusion: The developed scale provides a comprehensive and validated tool for assessing the teacher-student relationship, integrating key dimensions from multiple theoretical perspectives. This tool can be used for both research and practical applications, helping educators to foster positive interactions that enhance student engagement, achievement, and overall well-being. Future research should focus on further validation with diverse samples and explore the impact of cultural and contextual factors on these relationships.